A game theoretic approach for integrated pricing, lot-sizing and advertising decisions in a dual-channel supply chain. (5th April 2021) - Zarei, Javad; Rasti-Barzoki, Morteza; Hejazi, Seyed Reza
This paper discusses the coordination of pricing, lot-sizing and advertising policies in a dual-channel supply chain including one manufacturer and one retailer. The manufacturer produces one type of product and sells it to the retailer at wholesale price and also directly to consumers through direct channel. Consumers buy the product at retail price from the retailer and with direct sale price from the manufacturer. Demand depends on price and advertising efforts. Relationship between the manufacturer and the retailer has been modelled by two non-cooperative games of Nash and Stackelberg-retailer and one cooperative game. Finally, the change effect of the important parameters on the profit functions and the decision variables has been investigated. The results show that with increasing the cross-price sensitivity, the manufacturer's equilibrium profit for the two non-cooperative games increases. However, the increase in this parameter has no effect on the retailer's equilibrium profit.